Analysis of Employee Performance at the Sumedang Regency Fire Department UPT - Sumiati, Ai (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The focus of this study is to analyze the phenomenon of employee performance at the Sumedang Regency Fire Department. Performance analysis at the Sumedang Regency Fire Department UPT aims to determine the performance of employees at the Sumedang Regency Fire Department UPT in order to achieve the performance desired by the Fire Department UPT. The method used for this research is a qualitative method where the data is collected using purposive sampling, in accordance with the theory of Miles and Huberman in Sugiyono (2018: 247-252), the data will then be reduced, presented, and drawn conclusions. The analysis of employee performance at the Sumedang Regency Fire Department was assessed through the dimensions of quality, quantity, timeliness, effectiveness and independence. In conclusion, the performance of employees at the Sumedang Regency Fire Department is still not optimal. My suggestion is that good employee performance should be maintained and even improved, accuracy in work and punctuality in entering work are more considered. Overall, the performance of the employees at the Fire Department has been optimal, it must be maintained and improved in order to have a better performance.